2013
DOI: 10.1021/jp401764p
|View full text |Cite
|
Sign up to set email alerts
|

Oleylamine-Stabilized Gold Nanostructures for Bioelectronic Assembly. Direct Electrochemistry of Cytochrome c

Abstract: Methods to prepare ultrathin gold nanowires and monodisperse nanoparticles based on the intrinsic property of gold(I) ions to form aurophilic interactions stabilized by oleylamine and long-chain alkylamine have been widely explored. Due to the low thermodynamic stability of the high aspect ratio nanostructures, their conjugation and assembly into functional nanosystems have not been explored so far. One of the reasons for this is that the surface of the nanostructures is insulated by stabilization compounds, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…It was demonstrated that the reduction of the potentialdetermining ion, Au(I), on the nanostructure electrodes could be proceeded at potentials more negative than that for the planar metal electrode [117].…”
Section: Gold and Palladiummentioning
confidence: 99%
“…It was demonstrated that the reduction of the potentialdetermining ion, Au(I), on the nanostructure electrodes could be proceeded at potentials more negative than that for the planar metal electrode [117].…”
Section: Gold and Palladiummentioning
confidence: 99%
“…Accordingly, several strategies for the immobilization of enzymes have been assayed: covalent binding 15,16 , physical adsorption [17][18][19][20][21] or encapsulation within polymeric matrices 22 .…”
Section: Introductionmentioning
confidence: 99%
“…25 The electrocatalytic alcohol oxidation using Au as the catalyst is sensitive to the structure of the gold surface. 29,30 In this study, we use ultrathin Au nanowires synthesized using wet chemical means 31, 32, 33 as a catalyst for alcohol oxidation reactions. 26 Thus, it would be interesting to investigate the use of Au nanowire as a potential candidate for electrocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%